Longitudinal effect of emotional processing on psychological symptoms in women under 50 with breast cancer. Issue 1 (April 2019) - Martino, Maria Luisa; Gargiulo, Anna; Lemmo, Daniela; Dolce, Pasquale; Barberio, Daniela; Abate, Valentina; Avino, Franca; Tortoriello, Raffaele
Breast cancer is a potential traumatic event associated with psychological symptoms, but few studies have analysed its impact in under-50 women. Emotional processing is a successful function in integrating traumatic experiences. This work analysed the relationship between emotional processing and psychological symptoms during three phases of treatment (before hospitalization, counselling after surgery and adjuvant therapy) in 50 women under the age of 50 with breast cancer. Mixed-effects models tested statistical differences among phases. There were significant differences in symptoms during the treatments: the levels of anxiety decrease from T1 to T3 (0.046), while those of hostility increase (<0.001). Emotional processing is a strong predictor of all symptoms. Clinical implications are discussed.